Fine structures in interlaced magnetic flux ropes via Hall-MHD simulations - Ying-Dong Jia; Hairong Lai; Hanying Wei; Yi Qi; C. T. Russell; Yasong Ge; Tielong Zhang (AIP Advances)
Magnetic flux ropes are a fundamental component in both space and laboratory plasmas. We present a Hall-MHD simulation exploring the interaction between two isolated magnetic flux ropes under mesoscale solar wind conditions. The interaction interface is resolved with a resolution approaching the kinetic scale, to reveal unprecedented details of this process. As we replicate previous findings that such interactions can lead to the formation of two new ropes, we also find that magnetic reconnection occurs in multiple locations inside the central current sheet, leading to transient small flux ropes, which is qualitatively consistent with previous magnetospheric multiscale observations. Consequently, each field line undergoes multiple reconnections that alter its connectivity before it exits the current sheet. Later, each flux rope divides into two branches: the reconnected flux moving away from the current sheet to form the transition regions of the new ropes and the remnant flux sustaining the current sheet. For each magnetic flux rope (MFR), the core field reconnects after most surface fields are reconnected so that the reconnecting MFRs maintain a relatively symmetric shape. These results in unprecedented detail highlight the complex internal dynamics and call for further observational and theoretical studies.